Contraction intensity and sex differences in knee-extensor fatigability. (December 2017) - Ansdell, Paul; Thomas, Kevin; Howatson, Glyn; Hunter, Sandra; Goodall, Stuart
Abstract: Females are less fatigable than males during isometric contractions across various muscles and intensities. However, sex differences in knee-extensor fatigability remain relatively unexplored. Purpose: To determine the sex difference in performance fatigability for intermittent, isometric contractions of the knee-extensor muscles. Methods: Eighteen participants (10 males, 8 females) performed intermittent, isometric, knee-extensor contractions at 30% of their maximal voluntary force (MVC) for 30 min and in a separate session at 50% MVC until task-failure. During both fatiguing protocols a MVC was performed every 60 s and electromyography (EMG) was recorded during all contractions. Results: At task completion males had a larger reduction in MVC force for the 30% MVC task (−32 ± 15% vs. −15 ± 16%, P = 0.042) and the 50% MVC task (−34 ± 8% vs. −24 ± 1%, P = 0.045). Furthermore, for the 50% MVC task, females had a longer task duration (937 ± 525 s vs. 397 ± 153 s, P = 0.007). The rise in EMG activity and force fluctuations were more rapid for the males than females (P < 0.05). When participants were matched for strength post hoc (n = 10), a sex difference in fatigability for both tasks was still evident. Conclusions: Females were less fatigable than males during intermittent, isometric, knee-extensor contractions at moderate relative forces and this difference was independent of strength.